2018
DOI: 10.22515/ljbs.v3i2.1374
|View full text |Cite
|
Sign up to set email alerts
|

Techniques and Quality of 'Civil War: Whose Side Are You On?' Comic Translation

Abstract: The objectives of this study were to know the translation techniques and the assessment translation quality of Marvel comic series entitled Civil War: Whose Side Are You? (Part 1 and 2) in terms of accuracy, acceptability, and readability. This was a descriptive qualitative research and focusing on a single case as well as holistic research involving documents, i.e: the original and the translation books as the objective data and informants who gave assesment on the quality of the translation. The techniques o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…A study by Barezzi, Nabbaban, & Santosa (2018) used comic as the object of the study, the result showed that the quality of the translation in their study could be considered high. It was concluded that the use of the Padanan Lazim (Established Equivalent) technique provided a high contribution to quality translation results (Barezzi, Nababan, & Santosa, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Barezzi, Nabbaban, & Santosa (2018) used comic as the object of the study, the result showed that the quality of the translation in their study could be considered high. It was concluded that the use of the Padanan Lazim (Established Equivalent) technique provided a high contribution to quality translation results (Barezzi, Nababan, & Santosa, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The procedures are considered to be accurate because the translations sound natural to the TL readers. However, to further prove the credibility and accuracy, an assessment might be needed, as done by Barezzi et. al.…”
Section: B Class Shiftmentioning
confidence: 99%
“…In order to encapsulate the ways different perspectives about the evaluation of translation work by the assessor to evaluate objectively and effectively the quality of the final translation work, the translation quality assessment is undoubtedly needed. Furthermore, to improve the translation quality and to know whether the translated work is good or bad, its quality should be assessed (Kamil, 2014;Barezzi et al, 2018;and Admiati and Hartono, 2019). High quality of translation is achieved when the translation product meets certain standards and criteria.…”
Section: Introductionmentioning
confidence: 99%